Job Stress and Intention Turnover: Does Social Support Matter? - Padmantyo, Sri; Sabilla, Ardhinia Padmarani (Universitas Muhammadiyah Surakarta, 2017)
This research aims to investigate the effect of work stress on turnover intention with social support as a moderating variable. There are 53 respondents drawn with non-probability sampling. This research is analyzed by using validity test, reliability test, classical assumptions test, simple regression test, moderate analysis test, F test and t test. The results show that work stress has significantly positive effect on turnover intention while social support serves as its quasi moderator variable. Social support has positive and significant effect to turnover intention and it moderates work stress against turnover intention.